Two new restriction endonucleases from Proteus vulgaris. - Gingeras, T R (1981)
Two novel sequence-specific endonucleases have been isolated from Proteus vulgaris, ATCC 13315. PvuI recognizes the sequence: 5' C G A T decrease C G 3' 3' G C increase T A G C 5' and PvuII recognizes the sequence: 5' C A G decrease C T G 3' 3' G T C increase G A C 5' and cleave as indicated by the arrow (decrease). PvuI is an isoschizomer of XorII, RshI, and XniI. No enzyme with the specificity of PvuII has been described previously.